Assessment of clinical and laboratory parameters that reflect inflammatory response and organ function in sepsis (Faculty of Medicine Universitas Indonesia, 2005)
Sepsis is a spectrum of clinical conditions caused by the host immune response to infection or other inflammatory stimuli characterized by systemic inflammation. Clinical response to sepsis could be varies according to compensate or decompensate state, inflammatory process and host condition. Aims of this study is to assess the role of some parameters (clinical and biochemical, hematology, arterial blood gas analysis and coagulation) in supporting the diagnosis of sepsis. A cross-sectional study was performed in the Internal Medicine Inpatient Unit of Dr. Cipto Mangunkusumo National General Hospital, Jakarta, from February to July 2002. Forty-two patients who fulfilled the criteria of sepsis, severe sepsis, and septic shock were enrolled in this study. Clinical details and blood specimens for hematological, biochemical, arterial blood gas analysis and coagulation were collected. There were 42 subjects who participated in the study, aged from 19 to 78 years old. Eleven subjects fulfilled the criteria for early sepsis, 20 severe sepsis and 11 septic shock. Clinical examination showed that the Glasgow coma scale (GCS) was significantly reduced in severe sepsis and septic shock. Heart rate, respiration rate and body temperature were increased in all groups. Hemoglobin levels mostly below 10 g/dl and hematocrite levels below 30 %. The leucocyte counts were increased in more than 80%, mostly above 15.000/mm3. The platelet count were low (below 50.000/mm3) especially in septic shock. The serum creatinine were significantly increased (>2 mg/dl) in severe sepsis and septic shock. Albumin was decreased, lactate dehydrogenase/LDH and procalcitonin were increased. The arterial blood gas analysis showed that: pH and HCO3 were decreased especially in septic shock; the PO2 was lower in severe sepsis and septic shock; and PCO2 was below 32 mmHg in all groups. Coagulation examinations showed that fibrinogen was significantly decreased in septic shock; PT and APTT were prolong in severe sepsis and septic shock more than 18.8 and 48 seconds respectively. The d-dimer was also increased mostly in all groups. In conclusions that clinical examinations include level of consciousness, heart rate, mean arterial pressure, temperature and respiration rate and additional laboratory examinations include hamatological, biochemical, blood gas analysis and coagulation examinations can be used as parameters in diagnosis of sepsis. Some parameters include level of consciousness (Glasgow coma scale), serum creatinine, hemoglobin, platelet count and fibrinogen can differ sepsis according to severity. (Med J Indones 2005; 14: 26-32)Keywords: Clinical response, SIRS, sepsis